Evaluating the Impact of a Novel Competency-Based Education Workshop on Interns’ Perceived Preparedness in Providing Generalist End-of-Life Palliative Care - Nessa Keane; Riana Minogue; Maeve Brassil; Dympna Waldron; Eileen Mannion; Julien O’Riordan; Orla Mongan; Sharon Beatty (Palliative Medicine Reports)
Objectives: Palliative Care provision is a key competency for all physicians. Junior doctors are actively involved in the delivery of end-of-life care in hospitals despite often feeling unprepared to do so. There has been a recent shift toward competency-based education in palliative care. The primary aim of this study was to assess the impact of a novel competency-based workshop on interns’ perceived preparedness in providing generalist palliative care at end of life. Methods: A novel competency-based education workshop was designed by a multidisciplinary team including a medicine for the elderly consultant, the director of the intern training program, the hospital end of life coordinator, junior doctors and a palliative care consultant. The workshop consists of five interactive sessions delivered to interns over a three-week period by a member of the multidisciplinary team. The Palliative Care Competence Framework Questionnaire was administered pre and post completion of the workshop to examine the impact of the workshop on attitudes, behaviors, and knowledge. Results: Prior to the intervention, 86% (n = 38) of participants reported feeling inadequately prepared to manage death and dying to the level required in their role. Overall, there was a significantly positive improvement in attitudes (p = 0.0314), behavior (p ≤ 0.0001), and knowledge (p ≤ 0.0001) following the competency-based workshop among participants who completed the pre- and post-intervention questionnaires. Conclusions: The findings from this study suggest a novel competency-based workshop improved interns’ perceived preparedness in providing generalist palliative care at end of life. Future initiatives will focus on validating the findings of this study.